Can panpsychism solve thorny theological problems? - Miller, Tim B. (Religious studies, 2024)
Joanna Leidenhag has written a ground-breaking book arguing that the concept of panpsychism can solve several problems facing present-day humans. It can motivate greater commitment to concern for earth's diverse environments and the life forms that inhabit them. And it can solve theological problems connected with human consciousness, notably, how consciousness and matter coexist and interact. This article summarizes and comments on Leidenhag's arguments, then suggests several paths forward for those inspired by Leidenhag's ideas and arguments who wish to explore them and related notions in greater depth.